The Influence of Understanding Curriculum and Motivation on the Teacher’s Performance - Martita, Faulin; Lian, Bukman; Fahmi, Muhammad (Journal of Social Work and Science Education, 2024)
The purpose of this study is to find out and describe the influence of curriculum understanding and motivation on the performance of SMPN teachers in the Madang Suku III District. State Junior High School of Madang Suku III District, which consists of 3 (three) schools, including SMP Negeri 1 Madang Suku III, SMP Negeri 2 Madang Suku III, and SMP Negeri 3 Madang Suku III. The research method used in this study is a quantitative descriptive method. The population and sample in this study amounted to 59 teachers. Data collection techniques use questionnaires and documentation. The data analysis technique used a normality test, linearity test, multicollinearity test, simple correlation analysis, multiple correlation analysis, simple regression analysis, t-test, and F test. The results of this study were that there was a significant influence of curriculum understanding and work motivation on the performance of State Junior High School teachers in Madang Suku III District with an influence contribution of 59.6%.